Optimising Children's Education to Achieve a Sakinah Family through Family Planning in Hadith Perspective - Liddini, Laily (Qanun: Jurnal Hukum Keluarga Islam, 2025)
The phenomenon of weak child education in the family and the lack of public understanding of the concept of family planning (KB) in line with Islamic teachings are social problems that have an impact on the quality of Muslim family life. Many parents do not understand that early child education and careful family planning are strategic steps in forming a sakinah family. Departing from this issue, this study aims to examine the hadiths on child education and examine their normative implications for the concept of family planning in the perspective of Islamic law. The method used is qualitative with a literature study approach and descriptive-normative analysis. The hadiths analysed include the responsibility of parents in educating children and protecting offspring spiritually, ethically and socially. The results show that hadith-based child education is not only a moral guideline, but also has normative values that support proportional family planning practices. This is in line with the principle of ḥifẓ al-nasl in maqāṣid al-sharī'ah, namely maintaining the continuity and quality of generations. Family planning in the hadith perspective is seen as a shar'i strategy to build family resilience. The novelty of this research lies in the integration of child education and hadith-based family planning policies, which are still rarely discussed in Islamic family law studies. Theoretically, this research expands the normative understanding of hadith towards socio-religious policies, and practically provides a basis for the development of Islamic family planning programmes that support the formation of sakinah families in Indonesia.